Temporal patterns of endophytic microbial heterogeneity across distinct ecological compartments within the Panax ginseng root system following deforestation for cultivation - Shi, Zhenting; Yang, Limin; Yang, Meiling; Li, Kexin; Yang, Li; Han, Mei (Frontiers in Microbiology, 2024)
Alterations in the microbial community significantly impact the yield and quality of ginseng. Yet, the dynamics of microbial community shifts within the root endophytes of ginseng across varying cultivation periods remain inadequately understood. This study zeroes in on the microbial community variations within the xylem (M), phloem (R), and fibrous roots (X) of ginseng during the fourth (F4) and fifth (F5) years of cultivation, aiming to bridge this research gap. We assessed soil physicochemical properties, enzyme activities, and nine individual saponins, complemented by high-throughput sequencing techniques (16S rDNA and ITS) to determine their profiles. The results showed that cultivation years mainly affected the microbial diversity of endophytic bacteria in ginseng fibrous roots compartment: the ASVs number and α-diversity Chao1 index of bacteria and fungi in F5X compartment with higher cultivation years were significantly higher than those in F4X compartment with lower cultivation years. It is speculated that the changes of fibrous roots bacterial groups may be related to the regulation of amino acid metabolic pathway. Such as D-Glutamine and D-glutamate metabolism D-glutamine and D-glutamate metabolism, Cysteine and methionine metabolism regulation. The dominant bacteria in ginseng root are Proteobacteria (relative abundance 52.07%-80.35%), Cyanobacteria (1.97%-42.52%) and Bacteroidota (1.11%-5.08%). Firmicutes (1.28%-3.76%). There were two dominant phyla: Ascomycota (60.10%-93.71%) and Basidiomycota (2.25%-30.57%). Endophytic fungi were more closely related to soil physicochemical properties and enzyme activities. AN, TK, OP, SWC and EC were the main driving factors of endophytic flora of ginseng root. Tetracladium decreased with the increase of cultivation years, and the decrease was more significant in phloem (F4R: 33.36%, F5R: 16.48%). The relative abundance of Bradyrhizobium, Agrobacterium and Bacillus in each ecological niche increased with the increase of cultivation years. The relative abundance of Bradyrhizobium and Agrobacterium in F5X increased by 8.35 and 9.29 times, respectively, and Bacillus in F5M increased by 5.57 times. We found a variety of potential beneficial bacteria and pathogen antagonists related to ginseng biomass and saponins, such as Bradyrhizobium, Agrobacterium, Bacillus and Exophiala, which have good potential for practical application and development.